Assessing the quality of abstracts generated by ChatGPT for Philippine Journal of Librarianship and Information Science (PhJLIS) articles: a qualitative analysis - Posadas, Carl Benedict; Surmieda, Janny S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2024)
This study evaluates the feasibility of using ChatGPT, an advanced AI model, to generate abstracts for the Philippine Journal of Librarianship and Information Studies (PhJLIS). Focus group discussions with experienced librarians from the University of the Philippines Main Library assessed AI-generated abstracts against human-written ones, focusing on accuracy, brevity, and clarity. While AI-generated abstracts were found to maintain brevity and produce clear, structured summaries, they often lacked the nuanced understanding and specificity of human-authored abstracts. The research highlights the potential for AI to enhance abstract creation efficiency, but emphasizes the need for human oversight to ensure quality and relevance.
Thesis
Keywords: Philippine Journal of Librarianship and Information Science; ChatGPT -- Case studies; Generative artificial intelligence; Content analysis (Communication).; Natural language processing